Perception training approach for elite badminton players using visual obstacle - Kumar, P.; Kasthuri Thilagam, P.; Ajithkumar, L. (International Journal of Racket Sports Science, 2024)
Badminton is a fast-paced sport that requires not only physical fitness but also strong mental skills like anticipation and quick decision-making. This study introduces a new training method called "One-Way Mirror Perceptual Training", which uses a one-way mirror to block players' view of their opponent, forcing them to rely on their perception and reaction skills instead of visual cues. Twenty male badminton players aged 13-25 were divided into two groups: an experimental group that received the special training for six weeks and a control group that continued with regular practice. The training focused on improving agility, reaction time, coordination, and accuracy. Performance was measured before and after the training using tests like the Four Corner Run Test (FCRT) and agility drills. The experimental group showed significant improvement, with faster reaction times, better movement, and higher performance scores, while the control group had little change. These results suggest that the One-Way Mirror Perceptual Training helps players improve their mental and physical skills, making them more prepared for high-level competition. This study highlights the importance of including perceptual training in badminton and suggests that similar methods could be useful in other fast-paced sports.